The intratumoral administration of ferucarbotran conjugated with doxorubicin improved therapeutic effect by magnetic hyperthermia combined with pharmacotherapy in a hepatocellular carcinoma model - Jeon, Min Jeong (J Exp Clin Cancer Res, 2014)
BACKGROUND: Local hyperthermia of tumor in conjunction with chemotherapy is a promising strategy for cancer treatment. The aim of this study was to evaluate the efficacy of intratumoral delivery of clinically approved magnetic nanoparticles (MNPs) conjugated with doxorubicin to simultaneously induce magnetic hyperthermia and drug delivery in a hepatocellular carcinoma (HCC) model. MATERIALS AND METHODS: HCC cells expressing luciferase were implanted into the flank of BALB/c-nu mice (n = 19). When the tumor diameter reached 7–8 mm, the animals were divided into four groups according to the injected agents: group A (normal saline, n = 4), group B (doxorubicin, n = 5), group C (MNP, n = 5), and group D (MNP/doxorubicin complex, n = 5). Animals were exposed to an alternating magnetic field (AMF) to receive magnetic hyperthermia, and intratumoral temperature changes were measured. Bioluminescence imagings (BLIs) were performed before treatment and at 3, 7, and 14 days after treatment to measure the tumoral activities. The relative signal intensity (RSI) of each tumor was calculated by dividing the BLI signal at each time point by the value measured before treatment. At day 14 post-treatment, all tumor tissues were harvested to assess the apoptosis rates by pathological examination. RESULTS: The rise in temperature of the tumors was 1.88 ± 0.21°C in group A, 0.96 ± 1.05°C in B, 7.93 ± 1.99°C in C, and 8.95 ± 1.31°C in D. The RSI of the tumors at day 14 post-treatment was significantly lower in group D (0.31 ± 0.20) than in group A (2.23 ± 1.14), B (0.94 ± 0.47), and C (1.02 ± 0.21). The apoptosis rates of the tumors were 11.52 ± 3.10% in group A, 23.0 ± 7.68% in B, 25.4 ± 3.36% in C, and 39.0 ± 13.2% in D, respectively. CONCLUSIONS: The intratumoral injection of ferucarbotran conjugated with doxorubicin shows an improved therapeutic effect compared with doxorubicin or ferucarbotran alone when the complex is injected into HCC tissues exposed to AMF for magnetic hyperthermia. This strategy of combining doxorubicin and MNP-induced magnetic hyperthermia exhibits a synergic effect on inhibiting tumor growth in an HCC model.